Comparative Evaluation of Silver-Containing Antimicrobial Dressings on In Vitro and In Vivo Processes of Wound Healing - Hiro, Matthew E. (Open Science Company, LLC, 2012)
Objectives: To compare the in vitro and in vivo effects of silver products on wound healing. Methods: Eight silver products were compared to determine: fibroblast function using fibroblast-populated collagen lattices (FPCLs), fibroblast viability using the Trypan Blue exclusion test, and fibroblast mitochondrial activity using the MTT [yellow tetrazolium salt; 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] assay. In vivo effects of 9 silver products were evaluated utilizing a rat model of contaminated wounds. Serial quantitative bacteriology was performed on tissue biopsies over a 10-day period and serial wound areas were obtained over 12 days. Results: Fibroblast cytotoxicity occurred for all of the silver products evaluated. Remaining viable fibroblasts were insufficient to allow FPCL contraction. Mitochondrial activity of the fibroblasts allowed a separation of the various silver compounds. Actisorb Silver and Silvercel had the greatest viable fibroblast activity, but less than the control. Despite in vitro cytotoxicity, all of the silver products except Contreet Foam and Acticoat Moisture Control accelerated wound healing. Conclusions: Silver-containing dressings appeared to benefit healing of the wounds. Just as in vitro bacterial analyses do not fully predict the effect of an antimicrobial in the in vivo setting, in vitro cytotoxicity tests do not fully predict the effect of an agent on wound healing trajectories. Because of the varied antimicrobial and wound healing responses among products, a careful consideration of the particular effects of individual silver-containing dressings or drugs is warranted.